2008
DOI: 10.1007/s10863-008-9145-y
|View full text |Cite
|
Sign up to set email alerts
|

VDAC regulation: role of cytosolic proteins and mitochondrial lipids

Abstract: It was recently asserted that the voltage-dependent anion channel (VDAC) serves as a global regulator, or governor, of mitochondrial function (Lemasters and Holmuhamedov, Biochim Biophys Acta 1762:181-190, 2006). Indeed, VDAC, positioned on the interface between mitochondria and the cytosol (Colombini, Mol Cell Biochem 256:107-115, 2004), is at the control point of mitochondria life and death. This large channel plays the role of a "switch" that defines in which direction mitochondria will go: to normal respi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
156
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 203 publications
(163 citation statements)
references
References 78 publications
7
156
0
Order By: Relevance
“…1-3). VDAC is a mitochondrial outer membrane protein and is the key component of the PTP complex, which is responsible for mitochondrial metabolite flux (28,29). VDAC regulation of the opening or closing of the PTP pore is a determinant in mitochondria-mediated apoptosis and in the generation of redox potential (25).…”
Section: Discussionmentioning
confidence: 99%
“…1-3). VDAC is a mitochondrial outer membrane protein and is the key component of the PTP complex, which is responsible for mitochondrial metabolite flux (28,29). VDAC regulation of the opening or closing of the PTP pore is a determinant in mitochondria-mediated apoptosis and in the generation of redox potential (25).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is interesting as lipid-protein interactions are known to be important for the structure and function of integral membrane proteins (47)(48)(49)(50)(51)(52). In particular, VDAC1 gating and ionic selectivity have been shown to be dependent on lipid composition (53). Our MD simulations of mVDAC1 in a lipid bilayer demonstrated that a charge on E73 causes a perturbation of the surrounding membrane (Fig.…”
Section: μS-ms Dynamics Are Significantly Increased For the N-terminamentioning
confidence: 67%
“…Reconstitution experiments with the voltage dependent anion channel (VDAC) from the outer mitochondrial membrane have demonstrated an unexpected role of the abundant water-soluble protein, dimeric tubulin, in physiological regulation of mitochondrial function. 27,28 The model, proposed for the VDAC interaction with tubulin and confirmed by a number of specially designed experiments, [29][30][31] suggests that the negatively charged disordered tail of tubulin enters the net positively charged VDAC pore and thus blocks it for metabolite transport. Importantly, it was found that this interaction is influenced by the membrane composition, being very sensitive to the lipid species used for bilayer formation in VDAC reconstitution.…”
Section: Introductionmentioning
confidence: 91%